Perlindungan Hukum Bagi Pihak Yang Dirugikan Dalam Perjanjian Jual Beli Online Menurut Hukum Perdata Indonesia - Opa Jermias Matara; Benny Djaja; M. Sudirman (GLOBAL SCIENTS PUBLISHER, 2025)
This study discusses theiforms ofilegal protectionifor injured parties inionline sales agreements accordingito Indonesian civil law. The development ofiinformation technologyihas drivenisignificantichangesiin theitrading system, from conventional transactions to electronic transactions. However, this progress has also given rise to various legal issues, such as default, fraud, and a lack of transparency in the implementationiofiagreements. Theipurpose ofithis studyiisito determine how civil law provides protection for injured parties and how the legal resolution mechanisms are. Theiresearch methodiused isinormative legaliresearch withia statutoryiand conceptualiapproach, through a literature review of various primary, secondary, anditertiary legalisources. Theiresults showithat legaliprotectioniin online sales can be achieved throughithe applicationiof theiprinciple ofigoodifaith, the mechanism of default, and unlawful acts as regulated in theiCiviliCode. In addition, the recognition of the validity of electronic agreements iniLaw Numberi11 ofi2008 concerningiElectronic Informationiand Transactionsistrengthensithe legal position of parties in digital transactions. Disputeiresolution canibeipursued throughilitigation orinon-litigationichannels such as mediation and BPSK. This research confirms that the synergy between regulations, public legal awareness, and business actors' responsibilities is crucial in creating effective legal protection for parties harmed in online sales agreements.